Escobar syndrome with monodactyly: A rare case report - Somnath Karad; Imran Ahmad; Sudhanshu Tripathi; Sheikh Sarfraz Ali (Wolters Kluwer Medknow Publications, 2022)
Escobar syndrome (nonlethal type of multiple pterygium syndrome) is a very rare genetic disorder. The central manifestations of Escobar syndrome are the presence of multiple pterygia, fixed joint contractures, and characteristic facies. Here, we report a case of Escobar syndrome with additional features such as monodactyly and hypoplastic pectoralis muscle.